Planned Delivery Place Preferences among Pregnant Women Visiting Puskesmas Lempake - Muhammad Nur Huda; Ratno Ardianto; Nur Rohmah; Rahmat Bahtiar (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain key health indicators in Indonesia. According to data from the Indonesian Ministry of Health (2023), maternal deaths increased compared to the previous year. This study aimed to describe the delivery place preferences among pregnant women visiting Puskesmas Lempake and the factors influencing their decisions. Objective : To identify the characteristics and delivery place preferences planned by pregnant women attending Puskesmas Lempake Research Methods/ Implementation Methods : A descriptive quantitative study was conducted among all third-trimester pregnant women who visited Puskesmas Lempake in September 2025, with total sampling applied. Data were collected through structured questionnaires and secondary medical records. The data were analyzed using descriptive statistics of frequency and percentage Results : Most pregnant women were aged 20-35 years and had a senior high school level of educaction. Hospitals were the most preferred delivery places, followed by private clinics or independent midwives, and Puskesmas Lempake. Decisions regarding delivery place were primarily made by the pregnant women themselves and were largely supported by their husbands. Distance, cost, and family advice were the main reasons for choosing Puskesmas, while those who did not choose it cited inadequate facilities and previous clinical complications. Conclusion/Lesson Learned : The study highlights the need to strengthen health promotion and improve delivery facilities at Puskesmas Lempake. Increasing medical staff, particularly emergency doctors, and educating pregnant women and families about the importance of delivering at healthcare facilities are strongly recommended to reduce MMR and IMR.